Modulating effects of a decoction of a traditional Japanese herbal formula, hochuekkito (with Hedysari radix and Atractylodis rhizoma), on the local mucosal immune system of aged mice. Issue 3 (1st November 2019) - Kajita, Mieko; Saso, Kayako; Tanaka, Yosuke; Nagai, Takayuki; Kiyohara, Hiroaki
ABSTRACT: Aim: Hochuekkito is generally considered to express its clinical effects through modulation of the immune system. The formula using Hedysari radix and Atractylodis rhizoma as the component herbs, also has been used clinically as hochuekkito, but its immunopharmacological activity has not been clarified. Methods: Decocted extracts (0.1, 0.5 and 1.0 g/kg) were given to BALB/c mice intranasally immunized with influenza split vaccine, and influenza virus‐specific antibody titers were measured on ELISA together with transcriptome analyses with mRNA from uterus and lung. Results: Hochuekkito at lower doses (0.1 and 0.5 g/kg) increased influenza virus‐specific antibody titers in nasal washes, bronchoalveolar fluid (BALF), genital washes and feces. The higher dose (1 g/kg) of the extract, however, did not induce further increase of the antibody titer in BALF and genital washes. Furthermore, the extract inversely decreased the antibody titers in sera dose dependently. On transcriptome analysis, the 1 g/kg extract upregulated mRNA expression of co‐inhibitory receptors Pd‐1 and Lag3 in uterus but not in the lung. Meanwhile, the extract induced upregulation of the mRNA expression of marker molecules (CD163 and galectin‐1) related to M2 macrophages in lung. Conclusions: Hochuekkito with Hedysari radix and Atractylodis rhizoma modulates systemic and local mucosal immune systems in different ways. The formula encourages induction and recruitment of regulatory T lymphocytes and M2 macrophages in genital tract and lung, respectively, at the higher dose.